The Work-To-School Transition: Job Displacement and Skill Upgrading among Young High School Dropouts - Patrick Bennett (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper examines how and why returning to education fosters recovery from negative employment shocks among high school dropouts. High school dropout remains a problem, particularly as employment is increasingly skilled over time. Exploiting a policy expanding a Norwegian vocational certification scheme in a triple difference framework, workers displaced post-expansion certify their skills at significantly higher rates relative to those displaced pre-expansion. Increases in certification post-expansion significantly reduce income losses after job loss. Certifying skills fosters recovery among early career displaced workers through the retention of relevant industry-specific human capital, which increases job stability over 20 years later.
Keywords: J63; J65; I26; 330; job displacement; vocational education; unemployment